Six decades of publication performances and scientific maps on sports nutrition - Abdullah, Khairul Hafezad; Gazali, Novri; Abd Aziz, Fadzli Shah; Syam, Elgamar; Muzawi, Rometdo; Rio, Unang; Cendra, Romi; Nazirun, Novia (UIR Press, 2022)
A well-balanced diet is essential for individuals, particularly athletes, because it improves overall health by supplying energy besides repairing and replacing damaged cells. A well-balanced diet is also benefitting athletes to fuel their bodies before, during, and after training. This study aims to examine the intellectual structure of sports nutrition research using bibliometric measures from 1959 to 2021 based on the Scopus database. The study was investigated using SciMAT software, which employed keyword co-occurrence analysis to extract performance and scientific output vis-à-vis critical topics or themes in sports nutrition. The findings indicated that sports nutrition possesses enormous potential and growth potential. The most prevalent themes in this research area are trace elements, exercise, questionnaire, carbohydrate, and adolescent. Also, this study put up to analysing sports nutrition in countless fields, assisting in understanding its intellectual structure. Future researchers could use this data to identify the focus of awareness and make decisions in multiple ways. This study has a few limitations: 1) the researchers’ interpretation of the themes in this study was grounded on their knowledge; 2) this study only considered publication records from the Scopus database, and some sports nutrition publications may not have been included; and 3) if additional databases, such as Google Scholar, Microsoft Academics, or Dimensions, were accessed, the subject area may have shifted. The findings of this study should be accepted as a single evidence-based framework for developing future studies on sports nutrition research that will benefit researchers, practitioners, and policymakers.